Asuhan Keperawatan Nyeri Akut Pada Klien Dengan Hipertensi : Studi Kasus - Iswatun Iswatun (Universitas Muhammadiyah Lamongan, 2021)
Background: Hypertension is a disease that gets attention from all walks of life, considering that its impact requires comprehensive and integrated long-term treatment. Hypertension causes high morbidity (illness) and mortality (death).Objectives: This case study aims to carry out nursing care for clients who experience hypertension with the main problem being acute pain in the working area of the Sukodadi Health Center.Designe: This study design uses a case study method with a nursing process approach. The research subjects were 1 hypertensive client with the main problem being acute pain. The data collection technique was through interviews, observation, physical examination and documentation studies. Hypertensive patients were observed for 3 days of treatment. The data obtained were analyzed by comparing theories and cases. The data were analyzed using narrative analysis.Result: The results of the case study show that in the assessment there is a match between theory and literature review. Nursing diagnoses that arise in addition to acute pain, there is also a knowledge deficit. Nursing implementation is carried out based on interventions that have been made, both non-pharmacological (distraction and relaxation techniques) and pharmacological (collaboration in administering analgesics). In the evaluation there was a decrease in pain from a scale of 6 to a scale of 2.Conclusion: Implementation of non-pharmacological nursing (distraction and relaxation techniques), and pharmacology (collaboration in providing analgesics) and health education (reducing salt consumption, regulating diet, stress management, not smoking, not consuming alcohol, exercising, getting enough rest) can reduce pain and prevent recurrence. Keywords: Nursing care, acute pain, hypertension